Analisis Bentuk Dan Makna Kidung Turun Taun Dalam Penguatan Moderasi Beragama di Lombok - Ni Komang Wiasti (Jayapangus Press, 2022)
Lombok has very religious and unique local cultural wisdom, such as the art of the sacred religious hymn known as the Song of Down Taun where the texts are written in the Sasak language. The song is believed to be a medium of spiritual communication to invoke fertility for the Hindu people of Lombok. Precisely at Lingsar Temple, the song is often sung during the Piodalan ceremony, attended by the Sasak tribe and Hindus, as an actualization of strengthening religious moderation which has been passed down from generation to generation and exists as a form of moderate life attitude, mutual respect, tolerance, creating brotherhood for the sake of creating harmony. (spirit of harmony) in the Lingsar region. So far, the singers have only understood the metrum, the song, while the form and meaning have not been the focus of attention, so there is a need for an in-depth study of the form and meaning of the song Turun Taun in strengthening religious moderation. This research is qualitative, descriptive in nature, where the results of this research will later be described in the form of analysis, using symbol theory and meaning theory. The form of Kidung Turun Taun in strengthening religious moderation, the script uses Sasak language, by following the conventions for writing kidung in general, as in, lingsa, purwa kanti and tempo as is the case in the Wargasari ballad. The meanings contained in the song Turun Taun in strengthening religious moderation include: a) religious meaning; b) the meaning of welfare; c) the meaning of neutralizing disease; d) the meaning of loving culture; e) a unifying tool.